Quantum oscillations in β-Ag2Te and BiSbTeSe2 topological insulator systems - Azat Sulaev (2015)
In this thesis we are going to demonstrate that β-Ag2Te is a new topological insulator system with high electric field tunability and mobility. Our first-principles calculations show that β-Ag2Te is a topological insulator with a gapless Dirac cone with strong anisotropy. Observation and analysis of the 2D SdH oscillations and Aharonov-Bohm oscillations in β-Ag2Te devices confirm the existence of surface states. Highly anisotropic topological surface states of β-Ag2Te suggest that the material is a promising material for fundamental study and future spintronic devices. Also we will report the electric gate tuned in-plane anisotropic magnetoresistance (AMR) in nanoflake devices of topological insulator BiSbTeSe2 (BSTS). The AMR in BSTS is found to larger than that of transition metals, and shows tenability from negative to positive gradually when the Fermi level is manipulated to cross over the Dirac point by an applied gate electric field.